Exposure to anaesthetic agents does not affect multiple sclerosis risk. Issue 5 (24th January 2013) - Hedström, A. K.; Hillert, J.; Olsson, T.; Alfredsson, L.
<x xml:space="preserve">Abstract</x> Background and purpose It has been hypothesized that exposure to anaesthetic agents, some of which are chemically related to organic solvents, may affect the risk of developing multiple sclerosis (MS). The aim of this study was to estimate the influence of occupational exposure to anaesthetic agents on the risk for MS. We further aimed to investigate the impact of general anaesthesia and usage of nitrous oxide. Methods This report is based on two population‐based, case–control studies, one with incident cases (1798 cases, 3907 controls) and one with prevalent cases (5216 cases, 4701 controls). Using logistic regression, the occurrence of MS among subjects who have been exposed to anaesthetic agents was compared with that of those who have never been exposed by calculating the odds ratio with a 95% confidence interval. Results No association was found between occupational exposure to anaesthetic agents and risk of developing MS, also general anaesthesia or usage of nitrous oxide had no impact on MS risk. Conclusions Neither occupational exposure to anaesthetic agents, nor general anaesthesia or usage of nitrous oxide has any impact on MS risk and is safe also for people with a genetic susceptibility to the disease. However, further studies would be valuable in order to clarify whether other forms of organic solvents contribute to the triggering of MS.